Challenging gender inequality in tax policy making : comparative perspectives - Brooks, Kim (Oñati international series in law and society., 2011)
This volume takes a critical look at the gender of tax policy around the world. Contributors based in eight different countries examine the profound effects that gender norms and practices have had in shaping tax law and policy, and how taxation in turn impacts upon the possibilities for equality along gender, race, class, sexuality and other lines. Chapters explore how the gendered fiscal state might be theorised; how structural choices about rates and bases in tax policy design contribute to gender inequality; how tax policy affects family configurations and perceptions of what constitutes f.